Analysis of the Implementation of Hazard Identification, Risk Assessment and Risk Control (HIRARC) in the Work Environment Against Work Accidents (Case Study of PT XYZ) - Siregar, Ivana Maretha; Larasati, Aisyah; Muid, Abdul (Jurnal Ilmiah Teknik Industri, 2023)
PT XYZ, an aluminum smelting industry with high temperatures, has faced many near misses and accidents. This study aims to improve risk evaluation by analyzing the effect of the implementation and understanding of HIRARC on work accidents through the work environment. Data were collected from 179 respondents in the production section using purposive sampling and analyzed using the structural equation modeling method. The research results show that the implementation of HIRARC has a significant effect on the work environment, while the understanding of HIRARC is not significant. HIRARC implementation also affects work accidents, while the understanding of HIRARC is not significant. The work environment also influences work accidents. HIRARC implementation has an indirect effect through the work environment as a mediating variable, while understanding HIRARC has no indirect effect through the work environment. The recommendations proposed include installing blowers or shady areas with drinking water stations, using PPE, developing easy-to-understand OSH regulations and procedures, as well as implementing regular training, monitoring and evaluation.